Tanggung Jawab Pihak JNE sebagai Ekspeditur atas Kerugian yang Timbul Akibat Rusaknya Barang Elektronik Berupa HP Samsung Galaxy Note 7 yang Dikirim - St. Nadiyah Hudjaemah Parawansa (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
The purpose of this article is to find out how the liability of the JNE (Jalur Nugraha Ekakurir) as expeditor for the loss suffered by the sender (AM) for damage to the shipment (HP Samsung Galaxy Note 7) by using airline X is reviewed based on Act No. 1 of 2009 About Flight. The sender will hold JNE as the expeditor liability based on the expedition agreement, and the JNE as the expeditor will hold airline X liability based on the transport agreement. However, AM as the sender has violated the agreement, which is not correctly declared the item shipment, declaring that the item shipment is the HP Oppo F1 Selfie Expert, whereas the item shipment is HP Samsung Galaxy Note 7 which has been banned by the airline X. Accordingly, AM has violated violates article 1330 of the Civil Code, which is not fulfilling the clause